The difficulties of elementary teacher education students’ speaking performance: a comprehensive analysis - Ramadhani Uswatun Khasanah; Patria Handung Jaya (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2023)
Speaking English plays a fundamental role in personal development of students. However, many students struggle when speaking, which limits their capacity to communicate effectively and self-assuredly in a foreign language. The goal of this study is to investigate the elements influencing these difficulties in students' speaking abilities. To effectively design measures to improve kids' speaking abilities, educators and policymakers must have a thorough understanding of these challenges. This research also offers techniques to improve students' speaking abilities. This research used the qualitative research methodology. The data was gathered through observation, documentation, and interviews.  The findings demonstrate that the factors that influence the students’ difficulties are anxiety, low self-confidence, limited vocabulary, poor pronunciation, and grammar challenges. The strategies to enhancing the students’ speaking performance are building a supportive learning environment, improving vocabulary, using technology, and giving feedback to the students’ speaking performance. Thus, students and lecturers can contribute to create the strategies to enhance students’ speaking performance.